HEART SOUND AUSCULTATION USING MULTIPLE STETHOSCOPE - Yusri Khalil, Muhammad
Auscultation (Hearing human body’s sound) using stethosocope is one of many steps in physical examination for checking someone’s health status. A medical examiner doing auscultation to heart the sound of heart, lungs, and other sounds in the human body. Heart is one of the sounds that is heard by the medical examiner to identify the early diagnosis. In the process of auscultation, medical examiner hears the sound of the hearts fro four points which are located at the valves. Through that sound, medical examiner can give the early diagnosis to the patient. The weakness of this method is the subjectivity of medical examiner. The interpretation of the sound still depends on each of individual capacity. This weakness is caused by the acoustic sound which is produced by the heart is really small to be heard by human’s auditory system. Medical examiner also have to hear the sounds from multiple points that can lead to misinterpretation to each of point. Diagnosis that is given by the medical examiner is depends on sensitivity, accuracy and skill to understand and anaylise the sounds. Misinterpretation of the auscultation can lead to the misdiagnosis, especially in heart condition. Electronic stethoscope that is linked to the machine learning can make it easier for the user. But, that device need high computation ability and learning process that can help the device in determining the result. Furthermore, electronic device have a relatively expensive price that it is hard to be reached by the medical examiner. Other alternative is needed in the using of electronic stethoscope that can help the medical examiner to give the objective diagnosis and analysis method that doesn’t need high computation ability. So, in this research, the option that is used is the use of four stethoscopes to hear the heart sound at the same time so the objectivity of heart sound auscultation can increase by hearing at multiple points at the same time. From the result of the trial and analysis that is done by the process of recording of the heart sound at the areas can be done at the same time in one processs of the recording of the heart sound. Also, the prototype that receive the input from four sound recording channels can display the graphic that represents the appearing of heart sound that is recorded.